Leadership and Nationalism in Azerbaijan - Hasanli, Jamil, author.
1 online resource.
Keywords: Ali Mardan bey Topchibashov was a prominent politician, who played a crucial role in the history of Azerbaijan. One of the most striking personalities in the history of Azerbaijan, the founder of liberal ideas, and the first President of the Republic of Azerbaijan, he led the Muslim faction in the first Russian Duma and the Union of Muslims of Russia and was a central figure of the Caucasian aemigraes in Europe. This book analyses and presents the life of the first independent Azerbaijani political leaders. Based on extensive research from archives in Azerbaijan, France, Georgia, Russia (Moscow and Kazan) and the UK, some of which are newly accessible, it traces the political personality of Topchibashov as one of the largest Muslim leaders and founder of the Azerbaijan Republic. At the same time, it offers insights into the history of the formation and creation of the national consciousness of the Russian Muslims and tracks the challenges in the national and religious policy of the Imperial administration of the Soviet Union. The author sheds light on the significant problems of the Russian Empire (nationalities specifically) and global movements such as the post-World War I settlement and the difficulties of the many non-Russian groups that declared independence after the Bolshevik rise of power. Filling a lacuna in modern Azerbaijan history, this book will be of interest to academics working on Russian, Soviet, South Caucasus and Central Asian History, in particular Russian Empire, Muslim nations, and nationalism in Central Asia and the Caucasus.